Porcine pericardium as glaucoma implant tube coverage: an experimental study - Luciano Moreira Pinto; Caio V. Regatieri; Ivan Maynart Tavares; Moacyr Pezati Rigueiro (2008)
PURPOSE: To evaluate the inflammatory response associated with the use of processed porcine pericardium and glycerin-preserved homologous sclera as silicone glaucoma drainage device coverage in a rabbit experimental model. METHODS: Eight New Zealand white rabbits' eyes received an equal-sized glycerin-preserved homologous scleral patch or a double-layered processed porcine pericardium that was sutured to the bare sclera covering a silicone tube. Conjunctival hyperemia was graded using the double-blind method during the immediate postoperative period and during the first, third, and seventh postoperative weeks. After the seventh week, the enucleated eyes were histopathologically examined. They were also evaluated for signs of patch graft melting, tube erosion and chemosis. RESULTS: There was no occurrence of graft melting or tube exposure, although porcine pericardium was associated with greater inflammation through clinical observation. Light microscopy revealed marked inflammation surrounding the porcine pericardium with foreign body granuloma formation. On the other hand, the sclera group presented milder inflammation with foreign body granulomas only around the sutures. CONCLUSIONS: Porcine pericardium is associated with significant inflammation when used as tube coverage in a rabbit model, at both histopathologic and clinical levels, when compared to glycerin-preserved homologous sclera during the seven-week follow-up period.